Implementasi Algoritme Genetika Dalam Optimasi Knapsack Problem Penentuan Objek Wisata Wilayah Malang Raya - Abdul Fatih; Budi Darma Setiawan; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tourism has become commodity that can't be separated from human's life. There are some areas in Indonesia make tourism into the specific characteristics of their region which one is Malang Raya. The form of attention in the tourism sector is activated the building of new tourism objects. There was more tourism object than before will be more coddling for the tourists and also give a new problem. The tourist have knapsack problem which the tourist must decided all of tourism objects list that visited with the limited time. The optimization of knapsack problem can be resolved by using genetic algorithm. The genetic algorithm will make a formation of chromosome as representation of solution. The structures of genetic algorithm consist of initialization, reproduction, evaluation, and selection. The process of genetic algorithm did in the 50 generations with 100 populations whereas the pc value is 0, 7 and the value of pm is 0, 8. Result of processing genetic algorithm towards case study that has been tested gave the solution resemble to nearby tourism areas list and grouping in the certain areas.